Penyebaran Berita Hoaks Seputar Fatwa Haram Vaksinasi Covid-19: Studi Deskriptif Kualitatif Berita Hoaks Hasil Deteksi Kominfo yang Dirilis melalui Website: eppid.kominfo.go.id - Dikhorir Afnan (IQTIDA : Journal of Da'wah and Communication, 2022)
The reality today is that there are still many Indonesians who intentionally or unintentionally commit violations in the form of spreading false news or hoaxes. In the first quarter of the start of the Covid-19 vaccination program, the Ministry of Communication and Information noted that there were 117 false messages related to the Covid-19 vaccine spread among 634 uploads on various social media platforms. The purpose of this study is to describe any hoax news content that has ever gone viral in the community related to Covid-19 vaccination during the January 2021 period. The method used in this study is qualitative descriptive of certain phenomena based on data obtained in detail according to the problems specified. in research. As for the results of this study, there were 42 hoax news about Covid-19 vaccination during the January 2021 period. Of that number, the most spread of hoax news and disinformation occurred on January 18, 2021, namely six news.